2020
DOI: 10.1515/eng-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Application of virtual and augmented reality in automotive

Abstract: AbstractNowadays, virtual reality enters engineering work. It is widely used in various sectors. It brings new possibilities that result is increasing of productivity and reliability of production, quality of products and processes. One of the areas where virtual reality has been used more and more is logistics. Virtual reality and especially augmented reality offer above all in the area of logistics a perspective related with increasing of effectiveness of processes.Wide possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…These results are consistent with those shown by [13]. The automotive industry's relevance may be linked to the fact that virtual technologies have long been employed in this sector, being used in a variety of fields and applications, such as production, training, and maintenance, to name a few [44][45][46]. Furthermore, the automotive industry is one of the most mature manufacturing sectors, where cutting-edge technologies are often deployed for the first time [13].…”
Section: Application Fieldssupporting
confidence: 84%
“…These results are consistent with those shown by [13]. The automotive industry's relevance may be linked to the fact that virtual technologies have long been employed in this sector, being used in a variety of fields and applications, such as production, training, and maintenance, to name a few [44][45][46]. Furthermore, the automotive industry is one of the most mature manufacturing sectors, where cutting-edge technologies are often deployed for the first time [13].…”
Section: Application Fieldssupporting
confidence: 84%
“…These findings are congruent with those of [56]. The importance of the automobile industry may be related to the fact that virtual technologies have long been utilized in this sector in a range of specialties and applications, such as manufacturing, training, and maintenance, to mention a few [13,57,58]. Departments such as design, engineering, maintenance, and assembly are already using the technology to support practically everything in the automotive sector, from product development to task assistance in machine assembly or maintenance procedures.…”
Section: Application Fields and Methodssupporting
confidence: 67%
“…MR, including virtual reality (VR) and/or augmented reality (AR), has been implemented on a wide scale in the automotive industry. This technology has proven benefits for improving safety, performance, and product design, for better training, for the faster execution of activities, for error reduction, and for user satisfaction [34,35]. The literature review found that MR technology has been implemented to support human involvement in systems, also known as human cyber-physical systems (HCPS).…”
Section: Automotive Industriesmentioning
confidence: 99%